Nurses’ perceptions of patient handoffs and its predictors in public hospitals with specialists in Kelantan: a cross-sectional study - Nawawi, Mohd Hanif Mohd (2023)
Introduction: Understanding the significance of proper handoff process will help to reduce medical errors and enhance patient safety concerns. Thus, the purpose of this study was to investigate nurses' perceptions of patient handoffs in public hospitals with specialists in Kelantan and its predictors. Methodology: This cross-sectional study examined nurses from three specialist hospitals in Kelantan, Malaysia. The nurses were proportionately and randomly selected from the hospitals and included in the study. The nurses had at least six months of work experience and worked shifts at public hospitals with specialists in Kelantan. The study used a self-administered questionnaire with 26 items from six domains, which was validated and scored using a 5-point Likert scale. The data was analyzed using SPSS version 25 and linear regression analyses were used to identify predictors of nurses' perceptions of handoffs. Results: A total of 418 nurses participated in the study. The results indicate that nurses hold a positive view of handoffs, with a mean score ± SD of 3.53 ± 0.31. The mean age of the participants was 41.06 ± 6.26 years, the mean working experience was 16.80 ± 6.12 years and the mean handoff duration was 24.39 ± 10.68 minutes. The study identifies the paediatric department (95% CI: -0.195, -0.053, p <0.001), in-service formal training on handoff (95% CI: 0.016, 0.161, p <0.05) and satisfaction with the handoff process (95% CI: 0.234, 0.425, p <0.001) as the most significant predictors of nurses' perceptions. Conclusion: The study found that nurses generally perceived patient handoffs positively, with predictors including the paediatric department, handoff training and satisfaction with the process. To maintain good handoff practices, ongoing education, teamwork, audits and safety-focused culture are important.